Hypocalcemic tetany unveiling Vitamin B12 deficiency: A rare manifestation coupled with hyperventilation (Indian Journal of Case Reports, 2025)
Hypocalcemic tetany is a clinical condition characterized by involuntary muscle contractions and spasms due to low levels of ionized calcium in the blood, commonly associated with conditions such as hypoparathyroidism, Vitamin D deficiency, and chronic kidney disease. We report the case of a 16-year-old vegetarian girl who presented with recurrent episodes of tetany, muscle cramps, and fainting. Initial management with calcium supplementation and anxiolytics provided partial relief. But as tetany was recurrent, respiratory alkalosis was found to be the contributing factor. Anxiety-induced hyperventilation leads to respiratory alkalosis. Despite correction of alkalosis, tetany persisted, and the patient developed gait abnormality. Anxiety and gait abnormality were both found to be due to Vitamin B12 deficiency. Parenteral Vitamin B12 supplementation resulted in complete recovery from tetany, gait disturbance, and anxiety. Hence, this is a rare manifestation of Vitamin B12 deficiency, pertaining to anxiety-induced hyperventilation, leading to respiratory alkalosis and presenting clinically as recurrent tetany. Treatment only by parenteral calcium was not enough, and unmasking the hidden etiology of Vitamin B12 deficiency was key to recovery.